2021
DOI: 10.3390/ma14164488
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Mechanical Characteristics of Glass and Nylon Fiber Reinforced Peach Shell Lightweight Concrete

Abstract: In the current study, the utilization of glass and nylon fibers in various percentages are added to enhance the mechanical performance of peach shell lightweight concrete. Glass and nylon fibers were added at 2%, 4%, 6%, and 8% by cement weight. The results showed that, as we added the glass and nylon fibers, the density of peach shell concrete was reduced by 6.6%, and the compressive, split tensile and flexural strength were enhanced by 10.20%, 60.1%, and 63.49%. The highest strength that was obtained in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…This method is generally used when several input variables affect the output variable. Equation (1) (first-order model) was utilized to calculate the quantity of the experimentation [36].…”
Section: Cementmentioning
confidence: 99%
“…This method is generally used when several input variables affect the output variable. Equation (1) (first-order model) was utilized to calculate the quantity of the experimentation [36].…”
Section: Cementmentioning
confidence: 99%
“…Furthermore, water absorption generates freeze and thaw actions, which add stress to the surrounding concrete, resulting in less durable concrete. According to one study, water absorption is one of the reasons for alkali–silica reactions [ 88 ]. Figure 11 shows the water absorption of concrete with varying doses of waste glass as per past studies [ 49 , 60 , 72 , 89 , 90 ].…”
Section: Durabilitymentioning
confidence: 99%
“…It was also shown that dry shrinkage after 28 days (56 and 90 days) was almost equivalent to dry shrinkage at 28 days. It has also been observed that the dry shrinkage rate is higher in the first 7 days and decreases or remains constant with age [ 88 ]. The previous study has shown that coarse aggregate inhibits dry shrinkage, and dry shrinkage is caused mostly by the movement of cement mortar [ 55 ].…”
Section: Durabilitymentioning
confidence: 99%
“…Another advantage of these composites is the use of secondary mineral resources, such as microsilica, slag, fly ash, ground rocks, or stone dust [20][21][22][23][24]. The application scope of a strain-hardening cement composite (SHCC) depends on its strength and deformation characteristics [25][26][27][28][29][30]. The values of these characteristics are determined by properties of the cement matrix, microfiber, as well as by properties of the contact zone between matrix and microfiber [29,30].…”
Section: Introductionmentioning
confidence: 99%